The suppression of the probe laser pumping effect in SERF atomic magnetometer - Cao, Qian; Zhai, Yueyang; Huang, Binyue; Li, Renjie; Li, Jiajie (Frontiers in Physics, 2023)
Spin exchange relaxation free atomic magnetometer, as an ultra-highly sensitive magnetic field sensor, is limited by the performance of the probe laser system. The probe laser pumping effect (PLPE) hinders the increase in the performance of probe laser system. This study investigated the PLPE and proposed a method for suppressing the same. Through changes to the angle of a quarter wave plate and the addition of a triangular modulated magnetic field to the alkali atoms, the suppression point was determined. Further, related parameters were measured for different degree of polarizations of the probe laser, which confirmed that the influence of PLPE on the magnetic field was least at suppressed point.